Human diversity in education an integrative approach - Cushner, Kenneth; McClelland, Averil; Safford, Philip L. (New York McGraw-Hill, 2009)
Education in a changing society -- Multicultural education : historical and theoretical perspectives -- Culture and the culture-learning process -- Classrooms and schools as cultural crossroads -- Intercultural development : considering the growth of self and others -- Creating classrooms that address race and ethnicity -- The classroom as a global community : nationality and region -- Developing learning communities : language and learning style -- Religious pluralism in secular classrooms -- Developing a collaborative classroom : gender and sexual orientation -- Creating inclusive classrooms : the ability/disability continuum and the health dimension -- Creating developmentally appropriate classrooms : the importance of age and developmental status -- Improving schools for all children : the role of social class and social status in teaching and learning. Foundations for multicultural teaching; Multicultural teaching in action
Includes bibliographical references and index.
Keywords: Multicultural education -- United States; Individual differences in children -- United States; Sex differences in education -- United States; Giáo dục